Abortion in Cases of Zika Virus Congenital Infection - Vivian Maria Ribeiro Mota; Luciano Pamplona de Góes Cavalcanti; Alanna dos Santos Delfino; Thayse Elaine Costa Figueiredo Lopes; André Luiz Santos Pessoa; Erlane Marques Ribeiro (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2018)
Abstract The emergency in international public health caused by the Zika virus gave rise to the discussion about abortion in cases of congenital Zika virus syndrome (CZS). Therefore, we propose to carry out a bibliographic review on abortion in these cases. Five databases were searched using the following terms: abortion, miscarriage, and zika, with the interposition of the Boolean operator "AND." In the selected literature, we found references to the lack of information concerning the risks and severity of CZS, to the great psychological distress suffered by pregnant women, and to the risk of unsafe abortions as a justification for abortion in cases of CZS. However, it is necessary to have available tests that could diagnose, in the first trimester of pregnancy, that the fetus has been affected by the virus, and that it may have important limitations, in order to subsidize the qualified discussion about abortion in these cases.